Double microring resonators polymer wave guide for optical biosensing / Mohd Hazimin Mohd Salleh, Mohd Haziq M.Salleh and Muhammad Salihi Abd Hadi - Mohd Salleh, Mohd Hazimin; M.Salleh, Mohd Haziq; Abd Hadi, Muhammad Salihi (Universiti Teknologi MARA Cawangan Pahang, 2018)
The potential of double microring resonator polymer wave guide as an optical biosensor was demonstrated. Visible wavelength region at 632 nm is used as a centre wavelength because it is commonly used in biological and chemical sensing for both label and label-free sensing. The double microring resonator wave guide structure is simulated using COMSOL Multiphysics optical design and analysis software. The results show that there is a transmission drop with a 3 dB bandwidth of 631.4 nm when the surrounding refractive index is 1.33. The specific wavelength (output transmission) is shifted to 674.6 nm when the surrounding medium into 1.43, in order to imitate the bioanalytes solution. According to simulation result, the wavelength shift was approximately 43.2 nm for 0.1 increasing of surrounding refractive index. The double microring resonator polymer wave guide was fabricated by using electron beam lithography. Then, the fabricated devices were integrated into micro fluidic systems in order to validate the wavelength shift. From the experiments, the wavelength shift occurred approximately 32.3 nm over 0.1 increment of refractive index. Thus both simulation and experimental results strongly indicate that double micro ring resonator polymer wave guide structure at visible wavelength region have a potential for label or label-free optical biosensing applications.